Impact of Live Ligilactobacillus salivarius CCFM1332 and Its Postbiotics on Porphyromonas gingivalis Colonization, Alveolar Bone Resorption and Inflammation in a Rat Model of Periodontitis - Qing Hong; Yu Ren; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Shumao Cui; Zhenmin Liu (Microorganisms)
Periodontitis is a chronic inflammatory disease caused by periodontopathic bacteria such as Porphyromonas gingivalis (P. gingivalis), which leads to alveolar bone destruction and systemic inflammation. Emerging evidence suggests that probiotics may mitigate periodontal pathology. To systematically evaluate the alleviative effects and mechanisms of different forms of probiotics, including live bacteria and postbiotics, on periodontitis, we first screened and identified Ligilactobacillus salivarius CCFM1332 (L. salivarius CCFM1332) through in vitro antibacterial and anti-biofilm activity assays. Subsequently, we investigated its therapeutic potential in a rat model of experimental periodontitis. The results demonstrated that both live L. salivarius CCFM1332 (PL) and its postbiotics (PP) significantly reduced the gingival index (GI) and probing depth (PD) in rats, while suppressing oral colonization of P. gingivalis. Serum pro-inflammatory cytokine levels were differentially modulated: the PL group exhibited reductions in interleukin-17A (IL-17A), interleukin-6 (IL-6), and interleukin-1β (IL-1β) by 39.31% (p < 0.01), 17.26% (p < 0.05), and 14.74% (p < 0.05), respectively, whereas the PP group showed decreases of 34.79% (p < 0.05), 29.85% (p < 0.01), and 19.74% (p < 0.05). Micro-computed tomography (Micro-CT) analysis demonstrated that compared to the periodontitis model group (PM), the PL group significantly reduced alveolar bone loss (ABL) by 30.1% (p < 0.05) and increased bone volume fraction (BV/TV) by 49.5% (p < 0.01). In contrast, while the PP group similarly decreased ABL by 32.7% (p < 0.05), it resulted in a 40.4% improvement in BV/TV (p > 0.05). Histological assessments via hematoxylin and eosin (H&E) and tartrate-resistant acid phosphatase (TRAP) staining confirmed that both the PL group and the PP group alleviated structural damage to alveolar bone-supporting tissues and reduced osteoclast-positive cell counts. This study suggests that live L. salivarius CCFM1332 and its postbiotics reduce alveolar bone resorption and attachment loss in rats through antibacterial and anti-inflammatory pathways, thereby alleviating periodontal inflammation in rats.